2022
DOI: 10.1186/s12967-022-03595-1
|View full text |Cite
|
Sign up to set email alerts
|

The potential of mecciRNA in hepatic stellate cell to regulate progression of nonalcoholic hepatitis

Abstract: Background Nonalcoholic steatohepatitis (NASH) occupies a substantial proportion of chronic liver disease worldwide, of which pathogenesis needs further research. Recent studies have demonstrated the significant roles of circular RNAs (circRNAs) in NASH, while the function of a novel type of circRNAs, namely mitochondria-encoded circRNAs (mecciRNAs), remains elusive. Therefore, we aimed to investigate their potential to regulate the progression of NASH in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Our study found a significant relation between age of patient and stage of fibrosis with p value of 0.012. This finding coincides with Schuppan D., et al 9 , who found that the age of onset of infection has consistently been proven to be a primary factor impacting the pace of fibrosis advancement in hepatitis C, with the speed of fibrosis progression being directly connected with the age of onset of infection in fibrosis progression analyses. Immune factors, increased fibrogenesis, or decreased fibrolysis may be involved in the influence of age on fibrosis progression, although the precise mechanisms are unknown 10 Also Bhattacharya P. and Mukherjee S. 11stated that regular heavy alcohol consumption; age (>50-55 years); female gender; hispanic or white racial background; human leukocyte antigen DRB; HIV and other immune suppressive conditions; degree of steatosis; severity of inflammation; necrosis and injury; and a high iron load are all factors that enhance fibrosis and disease progression.…”
Section: Resultssupporting
confidence: 89%
“…Our study found a significant relation between age of patient and stage of fibrosis with p value of 0.012. This finding coincides with Schuppan D., et al 9 , who found that the age of onset of infection has consistently been proven to be a primary factor impacting the pace of fibrosis advancement in hepatitis C, with the speed of fibrosis progression being directly connected with the age of onset of infection in fibrosis progression analyses. Immune factors, increased fibrogenesis, or decreased fibrolysis may be involved in the influence of age on fibrosis progression, although the precise mechanisms are unknown 10 Also Bhattacharya P. and Mukherjee S. 11stated that regular heavy alcohol consumption; age (>50-55 years); female gender; hispanic or white racial background; human leukocyte antigen DRB; HIV and other immune suppressive conditions; degree of steatosis; severity of inflammation; necrosis and injury; and a high iron load are all factors that enhance fibrosis and disease progression.…”
Section: Resultssupporting
confidence: 89%
“…Our data also showed that TGF-β secreted by PBMC with the SEA treatment causes activation of the LX-2 cells and leads to the upregulation of hepatic fibrotic markers α-SMA and collagen 1. A recent study reveals that the expression of C-myc and Smad2/3 are upregulated in LPS-treated hepatic stellate cells, while the expression of recombinant thrombospondin 1 and phosphorylation of STAT3 is upregulated in the hepatocytes of mice with liver fibrosis [ 77 ]. Based on the above results, the CUB domain-containing protein 1 (CDCP1) screened at the 12th infection week seems to be worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, overexpression of hsa_circ_0008882 inhibited the release of cytokines after copper exposure, thereby playing a role in the regulation of inflammatory responses related to chronic respiratory diseases [ 33 ]. Because of the characteristics of sequence lengths and partial cytoplasmic localization, hsa_circ_0089763 acts as a powerful miRNA sponge [ 34 ]. hsa_circ_0062683 is proposed for the first time in this study to be involved in COPD and may be associated with clinical indicators such as age.…”
Section: Discussionmentioning
confidence: 99%